Northern Sea Route e-platforms: Tools for competitive development - IIgor Ilin; Svetlana Maydanova; Anastasia Levina; Aleksandr A. Lepekhin (Data Science in Maritime and City Logistics: Data-driven Solutions for Logistics and Sustainability. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 30, 2020)
Purpose: The current study purpose is preparation of proposals for the creation of digital services platforms, which could be provided on the Northern Sea Route as an international maritime transport corridor, on the basis of an existing maritime container industry e-platforms analysis, as well as on the basis of the transport market participants requirements for the composition and characteristics of services. Methodology: The problem is considered in terms of the Enterprise Architecture approach. This study uses TOGAF and the Capability Driven Approach (CDA), a modern approach to the information systems development. These approaches help in analyzing the peculiarities of global e-platforms from the perspective of aggregating the enterprise architecture components into a business capability and provide foundation for the suggested tools determination. Findings: Conducted studies suggest that the digital business ecosystems development is now widespread in the maritime container shipping industry, and e-platforms are an effective tool to ensure their performance. With the help of EA and CDA, it is possible to formulate proposals for e-platforms, based on the synthesis of transport market participants requirements. Originality: The NSR development as international transport corridor along with benefits at the same time is controversial for carriers for a number of reasons, including the need of the NSR competitiveness increase by providing service at the level usual for carriers. The results of this paper create a foundation for further researches of digital services development in Arctic maritime logistics.
urn:nbn:de:gbv:830-882.0115459; hdl:10419/228915; https://econpapers.repec.org/RePEc:zbw:hiclpr:30
Keywords: 650; Logistics; Industry 4.0; Supply Chain Management; Sustainability; City Logistics; Maritime Logistics; Data Science